Carbon Nanotube Based Magnetic Tunnel Junctions (MTJs) for Spintronics Application - Titus, Elby; Krishna, Rahul; Grácio, José; Singh, Manoj; Ferreira, Antonio Luis; Dias, Ricardo G (IntechOpen, 2011)
None